Employees' experiences of participating in a workplace-supported weight management service: a qualitative inquiry. Issue 2 (27th March 2020) - Staniford, Leanne Jane; Radley, Duncan; Gately, Paul; Blackshaw, Jamie; Thompson, Lisa; Coulton, Vickie
Abstract : Purpose: The purpose of this study is to explore public health employees' experiences of participating in a commercial weight management programme supported by their employers over a 12-week period. Design/methodology/approach: Semi-structured interviews were conducted with 28 employees who had participated in the programme (group-based or online). Findings: The main motivators for enquiring about and attending the programme were: the offer to attend the programme free of charge, the opportunity to kick start their weight loss efforts, to take part in an academic research study and the opportunity for "shared experiences" with their colleagues. Research limitations/implications: This study did not allow us to explore the reasons why some employees opted not to take up the opportunity for weight management support through their workplace. Further qualitative research with non-engagers would allow us to inquire about why employees might not engage with WM support and offer alternative strategies. Practical implications: Employers should facilitate their employees' efforts to lead a healthier lifestyle in the long-term creating employer health and safety policies that actively encourage healthy living and weight management. Improving employee health can contribute to increasing productivity, reducing stress and absenteeism. Originality/value: This paper presents a novel approach to facilitating employees' weight management. Employees perceived their employer-supported participation in a commercial weight management programme outside of their work setting as a positive experience that assisted their weight management efforts suggesting the acceptability and feasibility of this approach to addressing weight in the workplace.